A Global Exploratory Analysis of Men Participating in Gender-Based Violence Prevention. Issue 16 (August 2019) - Tolman, Richard M.; Casey, Erin A.; Allen, Christopher T.; Carlson, Juliana; Leek, Cliff; Storer, Heather L.
Organizations addressing gender-based violence (GBV) increasingly include men as partners in prevention efforts. However, little is known about men who get involved in those efforts and what specific actions they take. We present analyses of data from an international sample of men involved in gender-based prevention work that aimed to describe (a) the nature of participants' involvement in prevention efforts, in both formal programming and in their daily lives; (b) characteristics of engaged men, including gender and bystander-related attitudes and beliefs, and social networks; and (c) factors that sustain men's involvement in GBV movements over time. Comparisons across global regions for these variables were also conducted. A total of 379 male-identified participants above 18 who had attended a GBV event in the past year completed an online survey (available in English, French, and Spanish). Respondents represented all continents except Antarctica, although North America was over-represented in the sample. Overall, respondents scored well above North American norms for men on support for gender equality and recognition of male privilege, and this was true across all geographic regions. Men in all regions reported moderate support from friends and somewhat less support from male relatives for their involvement in GBV prevention. Respondents in all regions reported high levels of active bystander and violence-preventive behavior. The most commonly reported motivations for involvement in GBV prevention included concern for related social justice issues, exposure to the issue of violence through work, hearing a moving story, or disclosures about domestic or sexual violence. Results were mainly similar across regions, but when regional differences emerge, they tended to be contrasts between the global north and global south, highlighting the importance of cross-fertilization across regions and a willingness to adapt critical learnings in new geographic settings.